Teachers’ perception of the role of school administrators in motivating high school teachers - Paramboor, Jafar; Ibrahim, Mohd Burhan; Musah, Mohammed Borhandden; Al-Hudawi, Shafeeq Hussain Vazhathodi (MCSER-CEMAS-Sapienza University of Rome, 2015)
This study investigates the perceptions of high school teachers on the role of school administrators in motivating them. The study used survey method and distributed questionnaires to teachers of ten aided high schools in Malappuram Educational District of Kerala, India, using quota sampling technique. Descriptive statistics, independent sample t-test, ANOVA, correlation, and multiple regression analysis were performed to analyse the data. The findings demonstrate that while the level of motivation received by teachers was low, their job satisfaction was found to be moderate. Only two age groups differed in their job satisfaction level while there were no significant differences found among gender and academic qualifications. The findings also revealed a significant relationship between job satisfaction of the teachers and their perceived level of motivation received from the authority. Instructional field was the largest contributor to teachers’ job satisfaction followed by the welfare and career progression aspects. These findings imply that the District level school administrators, as well as the state Ministry of Education should cultivate proper awareness among the school administrators about their role in motivating their teachers being cognizant of at least the three dimensions on which this study focused.